2016
DOI: 10.23907/2016.053
|View full text |Cite|
|
Sign up to set email alerts
|

Additive Effects of Cointoxicants in Single-Opioid Induced Deaths

Abstract: A forensic drug database (FDD) was used to capture comprehensive data from all drug-related deaths in West Virginia, with deaths also included from the northern New England states of Maine, Vermont, and New Hampshire. All four states serve predominantly rural populations under two million and all have similar state medical examiner systems that employ statewide uniform death certification policies and practices. This study focused on 1482 single opioid deaths (fentanyl, hydrocodone, methadone, and oxycodone) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
7
2
Order By: Relevance
“…Polysubstance use (the concurrent use of multiple drugs) is a strong driver of overdose among people who use drugs and presents unique prevention challenges. Combining central nervous system depressants or stimulants with opioids have each been associated with increased risks for experiencing a fatal overdose (29)(30)(31)(32). Fatal overdoses involving stimulants (both cocaine and methamphetamine) and benzodiazepines have increased in recent years, and the majority of deaths involving these drugs have also involved opioids (33).…”
Section: Introductionmentioning
confidence: 99%
“…Polysubstance use (the concurrent use of multiple drugs) is a strong driver of overdose among people who use drugs and presents unique prevention challenges. Combining central nervous system depressants or stimulants with opioids have each been associated with increased risks for experiencing a fatal overdose (29)(30)(31)(32). Fatal overdoses involving stimulants (both cocaine and methamphetamine) and benzodiazepines have increased in recent years, and the majority of deaths involving these drugs have also involved opioids (33).…”
Section: Introductionmentioning
confidence: 99%
“…The literature review resulted in 207 articles, with a final inclusion of 84 papers ( Table S1, Supplementary Electronic Material ) [ 16 , 19 , 20 , 29 , 34 , 35 , 36 , 37 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
“…These cases were also naive/non-tolerant to methadone effects, confirming a synergic effect of multiple drug intake and absence of tolerance. A reduction of predicted opioid concentration has been shown in fatalities in which ethanol was co-consumed, disregarding its levels [ 71 , 93 ]. A similar analysis has been attempted by, e.g., Bernard et al [ 113 ], who showed decreasing concentrations in three groups represented by methadone-only victims, methadone combined with other drugs and fatalities mostly due to other drugs, although the difference did not reach a statistically significant level.…”
Section: Discussionmentioning
confidence: 99%
“…Any substance that can increase somnolence/sedation or cause respiratory insufficiency has the potential to augment and/or prolong the deleterious respiratory effects of opioids. Such substances include ethanol, benzodiazepines, benzodiazepine-like hypnosedatives, barbiturates, and various types of relaxants that can cause sedation and depress the body's hypoxemic and hypercapnic ventilatory drives (16, 52, 85, -101). Although these substances may have little respiratory depressant effect on their own, particularly when not consumed in excessive amounts, the use of these substances in combination with opioids has the potential to augment and/or prolong the deleterious respiratory depressant effects of opioids, and to also augment a stuporous or comatose condition.…”
Section: Discussionmentioning
confidence: 99%
“…Although these substances may have little respiratory depressant effect on their own, particularly when not consumed in excessive amounts, the use of these substances in combination with opioids has the potential to augment and/or prolong the deleterious respiratory depressant effects of opioids, and to also augment a stuporous or comatose condition. In many opioid-related deaths in which such cointoxicants are detected, oftentimes the opioid concentrations are lower than if the opioid was consumed in isolation (99). This finding is indicative of the cumulative respiratory depressant effects that multiple drugs can have on the body.…”
Section: Discussionmentioning
confidence: 99%